Implementation of Offline Augmented Reality for Handling Illiteracy Emergencies in Remote Elementary Schools in Southwest Papua - Jumriah, Titin; Septyani, Ninik; Oktaviana Legu Rema , Yasinta (Jurusan Pendidikan Teknik Elektro, 2026)
The persistence of early-grade illiteracy in remote areas of Southwest Papua highlights a significant gap in equitable access to educational resources, particularly in contexts with limited infrastructure, unstable electricity, and minimal Internet connectivity. Most technology-based learning approaches rely on digital access, making them less applicable in such environments. This study aimed to develop and evaluate an offline augmented reality (AR) learning medium to improve letter recognition skills among elementary school students in resource-constrained settings. This study employed a research and development approach based on the design-based research (DBR) framework, allowing for iterative refinement of the intervention through real classroom implementation. The study involved early-grade students from two remote schools, and data were collected using the Early Grade Reading Assessment (EGRA), System Usability Scale (SUS), classroom observations, and teacher interviews. Quantitative analysis was conducted using paired sample t-tests and effect size calculations. The findings indicated substantial improvement in students’ letter recognition abilities following the use of the offline AR media. Students with initially low literacy levels demonstrated notable progress, whereas usability results confirmed that the application was practical and accessible for use in low-resource classrooms. Statistical analysis further showed a strong positive effect of the intervention on learning outcomes.This study contributes to the field by demonstrating how AR can be adapted for offline use in remote educational contexts, providing an empirically grounded model for inclusive and scalable literacy interventions. The abstract clearly outlines the objectives, methods, instruments, and main results, but remains overly dense with percentage figures and result categories without adequate explanation of the methodological context. Claims of novelty (